2023
DOI: 10.3390/pharmaceutics15020553
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Super-Repressor IkB-Loaded Exosomes (Exo-srIκBs) in Chronic Post-Ischemia Pain (CPIP) Models

Abstract: Complex regional pain syndrome (CRPS) is a condition associated with neuropathic pain that causes significant impairment of daily activities and functioning. Nuclear factor kappa B (NFκB) is thought to play an important role in the mechanism of CRPS. Recently, exosomes loaded with super-repressor inhibitory kappa B (Exo-srIκB, IκB; inhibitor of NFκB) have been shown to have potential anti-inflammatory effects in various inflammatory disease models. We investigated the therapeutic effect of Exo-srIκB on a roden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These are human embryonic kidney cell lines that are easy to manipulate and show high growth capacity; therefore, they are commonly used to produce therapeutic proteins or exosomes in human medicine [33,58]. We used the engineered exosome loaded with srIκB, a nondegradable form of IκB that prevents the nuclear translocation of NFκB [59]. NFκB is one of the most important regulators of proinflammatory gene expression and is highly activated at sites of inflammation in diverse diseases [60].…”
Section: Discussionmentioning
confidence: 99%
“…These are human embryonic kidney cell lines that are easy to manipulate and show high growth capacity; therefore, they are commonly used to produce therapeutic proteins or exosomes in human medicine [33,58]. We used the engineered exosome loaded with srIκB, a nondegradable form of IκB that prevents the nuclear translocation of NFκB [59]. NFκB is one of the most important regulators of proinflammatory gene expression and is highly activated at sites of inflammation in diverse diseases [60].…”
Section: Discussionmentioning
confidence: 99%
“…[ 226 ] treated post-ischemic mice with srIκB-loaded exosomes to suppress the NF-κB signaling cascade activated during kidney ischemia–reperfusion injury. Recently, these srIκB-loaded exosomes were also employed to suppress inflammation in models of alcohol-associated liver disease [ 227 ] and neuropathic pain [ 228 ].…”
Section: Methods For Intracellular Protein Deliverymentioning
confidence: 99%
“…56 Animal studies have yielded similar findings, as demonstrated by a significant upregulation of proinflammatory mediators and chemokines in the plantar, spinal dorsal horn (SDH), and DRG of rats in the chronic post-ischemia pain (CPIP) model of CRPS. [57][58][59] Furthermore, upregulation of NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome expression has been observed in the spinal dorsal horn of rats with CPIP. Inflammasomes play a crucial role in the occurrence and development of cytokine-mediated chronic pain, with proinflammatory cytokines IL-1β and IL-18 being the primary products of neutrophilic alkaline phosphatase (NALP) 1 and NLRP3 inflammasomes.…”
Section: Cytokinesmentioning
confidence: 99%